ANALISIS PENDAPATAN HOME INDUSTRY GULA MERAH KELAPA DI DESA PASIANG - Syarif, Syarif; Hamsiah, Hamsiah; Hikmah, Aulia Nurul; Dambe, Jumriani; Ansyar, Ansyar; Hamsah, Hamsah (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2024)
Matakali sub-district is one of the largest coconut producers with a coconut land area of 1,429.19 hectares and an annual production of 1,093.77 tons. This is a great opportunity for the coconut palm sugar home industry in Matakali sub-district, especially in Pasiang village. Based on the results of preliminary observations in Matakali sub-district, the coconut palm sugar home industry is only found in Pasiang village, and there are a total of 30 coconut palm sugar home industries in three hamlets namely Buttulamba, Tabone, and Seppong. This has brought changes to the utilization of coconut trees, which in the past were only used for their fruit to produce oil and copra, but now coconut trees are also used for their sap to make brown sugar. This is done because the community considers the market opportunity for coconut palm sugar to be better than the coconut oil or copra market. In addition, coconut fruit processing also has a harvest period, but coconut sap can be produced every day. The coconut palm sugar home industry in Pasiang village is currently in the development stage along with increasing market demand from outside the region. The purpose of this study was to determine the income level of the coconut brown sugar home industry in Pasiang Village, Matakali District, Polewali Mandar Regency. The analysis method used is quantitative analysis. The sampling technique used is saturated sampling technique, which is a method that uses the entire population as a sample. The data analysis technique used is income analysis. Based on the survey results, the average income of the red coconut sugar home industry is Rp 4,368,964 by month.